2019
DOI: 10.1021/acs.langmuir.9b00539
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide–Layered Double Hydroxide Composite Material for Adsorption–Photocatalysis of Water Pollutants

Abstract: Although adsorption has gained favor among numerous water treatment technologies as an effective pollutant removal method, its application is often hindered by challenges with its resource- and energy-intensive regeneration procedure once the available adsorption sites are exhausted. Herein, we present adsorption–photocatalysis composite materials combining layered double hydroxides (LDHs) and titanium dioxide (TiO2) for water treatment. Incorporation of the photocatalyst into the material opens opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 52 publications
1
20
1
Order By: Relevance
“…This value is close to the transport number of anions in bulk solution, which could be explained by the higher diffusion coefficient of the anions (∼2 × 10 –9 m 2 s –1 for Cl – , Br – , and I – ) compared to the cation (∼1.3 × 10 –9 m 2 s –1 for Na +61 ), indicating that the TiO 2 ALD film shows a negligible selectivity between Na + and these anions. This unselective transport is consistent with the near neutral charge of TiO 2 at the experimental pH (5.7) and implies that there is negligible interaction between TiO 2 and the Na + , Cl – , Br – , or I – ions.…”
Section: Resultssupporting
confidence: 81%
“…This value is close to the transport number of anions in bulk solution, which could be explained by the higher diffusion coefficient of the anions (∼2 × 10 –9 m 2 s –1 for Cl – , Br – , and I – ) compared to the cation (∼1.3 × 10 –9 m 2 s –1 for Na +61 ), indicating that the TiO 2 ALD film shows a negligible selectivity between Na + and these anions. This unselective transport is consistent with the near neutral charge of TiO 2 at the experimental pH (5.7) and implies that there is negligible interaction between TiO 2 and the Na + , Cl – , Br – , or I – ions.…”
Section: Resultssupporting
confidence: 81%
“…This provides further evidence that electrostatic interaction between the LZH surface and the negatively charged phosphate species did not play a dominant role in the adsorption process as it becomes less effective aer monolayer adsorption. 43 It could be said here that the adsorption of phosphate species was likely not limited to the external surface but the intercalation of the phosphate into the interlayer of the layered structure as well. 25,44 This is further supported by the intra-particle diffusion studies shown in the previous section.…”
Section: Adsorption Isothermsmentioning
confidence: 86%
“…Furthermore, Paredes et al (2011) [34] report that a TiO 2 /LDH matrix produced a synergistic effect causing both higher •OH radical production and higher degradation of phenol than TiO 2 alone. Similarly, the application of an LDH-TiO 2 matrix for dimethyl phthalate and methylene blue pollutant removal has also been reported [35,36], as well as the use of an LDH-TiO 2 matrix for the removal of 2,4-dichlorophenoxyacetic acid and orange II [37,38]. This clearly indicates improvement in both adsorption and photocatalysis of several aqueous pollutants when using a combined LDH-TiO 2 system.…”
Section: Introductionmentioning
confidence: 65%